Article 242 of the Criminal Code of the Republic of Belarus as an element of the criminal bankruptcy counteract system - Zakhilko, Kiryl S. (Journal of the Belarusian State University. Law, 2019)
This article deals with the use of Article 242 of the Criminal Code as an element of the criminal bankruptcy counteract system. The criminal bankruptcy norms system and some of its defects are analyzed. The pattern of use by law enforcement officer of some related to Article 238–241 Criminal Code of Criminal Law to counter criminal bankruptcy are substantiated. System properties of Article 242 of the Criminal Code and the criminal bankruptcy norms are identified. On the basis of the system proposals for improving the norms on criminal bankruptcy and Article 242 of the Criminal Code are formulated.